Pilot Study and Gamification Analysis of a Theory-based Exergame - Kaile Kubota; Elina Säteri; Tapani N. Joelsson; Tuomas Mäkilä; Sanna Salanterä; Anni Pakarinen (Serious Games Society, 2022)
A theory-based exergame was developed for tweens to promote their self-efficacy towards physical activity and increase their physical activity levels. We used protocols from both health science and gamification research in piloting the exergame. First, we assessed the usability and feasibility of the exergame and conducted a preliminary exploration of its effectiveness. After technical improvements were made based on our findings, we reiterated the pilot study and analysed the gamification elements of the exergame by using Octalysis analysis. The overall findings suggest that a theory-based exergame can positively influence the self-efficacy of tweens towards physical activity. The exergame showcased theoretical strength, achieved using diverse gamification elements but its overall game design and usability can be further improved. The study concludes that health-related components of the purpose of intervention must be incorporated in parallel with the engaging design of the game, taking into utmost consideration the theories, evidence as well as the needs and perceptions of its target users. This study provides valuable insights on future development and evaluation of gamified health interventions.